A regional exploration of retail visits during the COVID-19 pandemic. Issue 1 (1st January 2021) - Ballantyne, Patrick; Singleton, Alex; Dolega, Les
ABSTRACT: Despite evidence that the COVID-19 pandemic has precipitated significant regional (economic) inequalities, there is a substantial lack of regional insight into the impacts of COVID-19 on the retail sector. In this study, using data from SafeGraph, we adopt a regional approach to explore how visits to retail places changed during the early weeks of the COVID-19 pandemic in the Chicago Metropolitan area. In particular, we highlight that retail visits exhibited interesting spatio-temporal and structural trends.